Design of an Educational Application for Conservation and Ornamental Fish Capture Areas Based on Android - Mauli Kasmi; Tien Kumalasari; Syamsul Marlin Amir; Budiman; Arif Fuddin Usman; Wahyuddin; Ilham Ahmad; Andryanto Aman (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
This research aims to design an educational application about conservation and ornamental fish capture areas in Pangkajene Islands Regency. The application is developed based on the Android operating system to facilitate access and usage for the community. In the testing process, the application will undergo unit testing and compatibility testing to ensure that every part of the application works correctly and can be used smoothly on various devices and operating systems. The application will provide information about the conservation and ornamental fish capture areas in Pangkajene Islands Regency, including the types of ornamental fish and how to conserve the aquatic ecosystem in the area. With the presence of this application, it is expected to provide useful information for the community and increase awareness about the importance of preserving the aquatic ecosystem and understanding the concept of conservation and ornamental fish capture areas. Through unit and compatibility testing, it is expected that the application will work correctly and can be used smoothly on various devices and operating systems.